Facility Type is Associated with Margin Status and Overall Survival in Patients with Resected Intrahepatic Cholangiocarcinoma - Lee, Grace C. (Ann Surg Oncol, 2019)
BACKGROUND: Many studies have demonstrated associations between surgical resections at academic centers and improved outcomes, particularly for complex operations. However, few have examined this relationship in intrahepatic cholangiocarcinoma (ICC). The hypothesis of this study is that facility type is associated with improved postoperative outcomes and survival in patients with ICC who undergo resection. METHODS: Patients with stage I-III ICC who underwent hepatectomy were identified using the NCDB (2004-2014). Facilities were categorized as academic or community centers per Commission on Cancer designations. High-volume hospitals were those that performed ≥11 hepatectomies/year. Multilevel logistic mixed-effects models and parametric survival-time models were used to determine predictors of outcomes and overall survival (OS), respectively. RESULTS: A total of 2,256 patients were identified, of whom 423 (18.8%) patients were treated at community centers and 1,833 (81.3%) at academic centers. Nearly all high-volume centers were academic facilities (98.5% academic vs. 1.5% community), while low-volume centers were mixed (65.5% academic vs. 34.5% community) (p<0.001). Undergoing surgery at an academic center was an independent predictor of decreased positive margins (OR 0.71, 95% CI 0.51-0.98, p=0.04), lower 90-day mortality (OR 0.62, 95% CI 0.39-0.97, p=0.03), and improved OS (HR 0.78, 95% CI 0.63-0.96, p=0.02). Facility hepatectomy volume was not independently associated with any short-term or long-term outcomes. CONCLUSIONS: Treatment at an academic center is associated with fewer positive resection margins, decreased 90-day mortality, and improved OS in patients who undergo ICC resection. Facility surgical volume was not significantly associated with any postoperative outcomes after adjusting for patient and disease characteristics.